2019
DOI: 10.3390/soilsystems3040071
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Soil Carbon Fractions Using a Field Spectroradiometer Equipped with an Illuminating Contact Probe

Abstract: This research compared the accuracy of laboratory reference measurements of soil C and N fractions with soil reflectance spectra acquired using a portable field spectroradiometer with an illuminating contact probe. Soil samples were taken from eight, 1.6 ha watersheds, located in El Reno, Oklahoma on native warm season grasslands and agronomic managements with landform complexes serving as replicates within and among treatments. Soil samples were taken from 0–30-cm. Measurements included total soil organic car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The research reported herein is an extension of our previous work reported in Fortuna et al [15], but correlates the same variables (TSOC, total soil N (TSN), ROC, POMC and particulate soil N (POMN) to the HDR data collected only in the VIS-NIR region of the spectrum. Our analysis also evaluates VIS-NIR HDR data acquired not only from the high-end PSR + 3500 spectroradiometer, but also that from comparatively inexpensive and low S-N-R proximal (low-end) sensors.…”
Section: Introductionmentioning
confidence: 53%
See 4 more Smart Citations
“…The research reported herein is an extension of our previous work reported in Fortuna et al [15], but correlates the same variables (TSOC, total soil N (TSN), ROC, POMC and particulate soil N (POMN) to the HDR data collected only in the VIS-NIR region of the spectrum. Our analysis also evaluates VIS-NIR HDR data acquired not only from the high-end PSR + 3500 spectroradiometer, but also that from comparatively inexpensive and low S-N-R proximal (low-end) sensors.…”
Section: Introductionmentioning
confidence: 53%
“…Details of collection and processing of the soil samples used in this study are found in Fortuna et al [15]; therefore, only a brief summary is provided here. The soil samples were collected from three 1.6 ha sized watersheds at the USDA-ARS Grazinglands Research Laboratory, located in El Reno, OK, USA (35 • 32 28 N, 98 • 02 56.5 W).…”
Section: Soil Samplesmentioning
confidence: 99%
See 3 more Smart Citations